Risk assessment and responses to deteriorating patients: Nurses and junior doctors’ knowledge, attitudes and practice (KAP) in the East Coast Malaysia - Mohamed Ludin, Salizar; Ruslan, Rusila; Al- Mahmood, Sinan; Mat Nor, Mohd Basri (Malaysian Nurses Association, 2016)
Background: Nurses and junior doctors play an important role in providing care to patients, therefore their knowledge, attitudes and practice in assessing such patients are crucial to patient outcomes. Lately, concern about the incidence of deteriorating patients has increased, especially in the ward setting. High numbers of intensive care unit admissions are due to the transfer of deteriorating patients from medical wards. Purpose: To determine nurses‟ and junior doctors‟ knowledge, attitude an pratice in of assessment and treatment of deteriorating patients in medical wards, and their attitude toward, assessment of, and care practice with these patients. Method: A cross-sectional survey was used to collect data among nurses and junior doctors (n=191) in medical wards in three Malaysian East Coast hospitals in 2015. Data was analyzed using SPSS 22.0 for descriptive and inferential analysis. Findings: The study had a 79.5% response rate. Nurses and junior doctors perceived a good attitude and practice in assessing deteriorating patients. However, poor knowledge on assessing deteriorating patients found. Age was associated with KAP in relation to assessing deteriorating patients, and knowledge of emergency pharmacotherapy. Conclusion: Nurses‟ and junior doctors‟ lack of knowledge about emergency pharmacotherapy and assessing deteriorating patients, despite demonsrating good practice and a good attitude, must be addressed. There is a need for educational strategies to ensure that nurses and junior doctors have commensurate levels of theoretical and practice knowledge.